Environmental concentrations of antibiotics impair zebrafish gut health. (April 2018) - Zhou, Li; Limbu, Samwel Mchele; Shen, Meilin; Zhai, Wanying; Qiao, Fang; He, Anyuan; Du, Zhen-Yu; Zhang, Meiling
Abstract: Antibiotics have been widely used in human and veterinary medicine to both treat and prevent disease. Due to their high water solubility and low bioavailability, many antibiotic residues have been found in aquatic environments. Fish are an indispensable link between the environmental pollution and human health. However, the chronic effects of environmental concentrations of antibiotics in fish have not been thoroughly investigated. Sulfamethoxazole (SMX) and oxytetracycline (OTC) are frequently detected in aquatic environments. In this study, zebrafish were exposed to SMX (260 ng/L) and OTC (420 ng/L) for a six-week period. Results indicated that exposure to antibiotics did not influence weight gain of fish but increased the metabolic rate and caused higher mortality when treated fish were challenged with Aeromonas hydrophila . Furthermore, exposure to antibiotics in water resulted in a significant decrease in intestinal goblet cell numbers, alkaline phosphatase (AKP), acid phosphatase (ACP) activities, and the anti-oxidant response while there was a significant increase in expression of inflammatory factors. Antibiotic exposure also disturbed the intestinal microbiota in the OTC-exposed group. Our results indicated that environmental antibiotic concentrations can impair the gut health of zebrafish. The potential health risk of antibiotic residues in water should be evaluated in the future. Graphical abstract: Image 1 Highlights: Environmental concentrations of SMX and OTC increased the metabolic rate of fish. SMX and OTC increased fish mortality rates after Aeromonas hydrophila challenge. Exposure to SMX and OTC impaired intestinal structure and function. Exposure to SMX and OTC altered the intestinal microbiota composition. Abstract : Environmental antibiotic concentrations can impair the gut health of zebrafish.